Flexibility training for sprint runners - Blazevich, A. J. (Strength and Conditioning Journal, 2001)
Flexibility is important not only for the prevention of injury but in optimizing athletes' performances. It is important for athletes who perform sprint running as part of their sport to not only perform basic hip extensor/flexor, knee extensor/ lexor, adductor, calf/ankle, and upper body stretches but to include a number of specific stretches. The stretches described above should allow greater freedom of movement and may result in an increase in running speed and efficiency and a decrease in injury. It must be remembered, however, that athletes with specific injury concerns should consult a sports physician.